An approach to the diffusion of tacit knowledge: learning from imitation to creation. Issue 2 (16th March 2020) - Ding, Weixu; Aoyama, Atsushi; Choi, Eugene
Knowledge has been classified into two types as explicit and tacit knowledge. With the development of information technology, explicit knowledge could be coded and stored into databases. It seems difficult to use data processing to code tacit knowledge; since some tacit knowledge from personal experience and feelings are tough to be expressed or written into the documents. Several scholars believe that tacit knowledge has essential value for organisational members' problem-solving. Hence, this research attempts to explore the efficient methods to learn tacit knowledge. Inspired by the traditional craftsmen's learning approach from imitation to creation, this research utilises empirical methods to analyse 131 samples from Chinese corporations and proves that this learning method also has practical meaning for today's organisational learning. The findings show that individuals can learn tacit knowledge via imitating, adapting to the current situation, and then creating new ideas to solve problems. This research has proved that adaptive learning has a mediational role in the relationship between imitation and creation.